2014 Eighth International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing 2014
DOI: 10.1109/imis.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Architecture Reconfiguration in Pervasive Environment: An AADL-based Approach

Abstract: In the pervasive environment, in order to adapt to dynamic environments and changeable requirements, the architecture reconfiguration has drawn great attention, which includes structural, behavioral, and configuration aspects. Unfortunately, traditional architecture description methods are always static, and as such fail to completely specify the reconfiguration. In this paper, AADL (Architecture Analysis and Design Language) is applied to describe the dynamic architecture. First, with features of AADL, the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Early research on social connection identified the importance of an individual's perception of social inclusion as the determinant of belonging or loneliness (Cacioppo & Patrick, 2008). Perceived community support can increase resilience, enhance the evaluation of personal resources (Layous & Nelson-Coffey, 2020) and increase exercise motivation (Chen et al, 2014). A recent measure of community perception is the construct of KM.…”
Section: Km As Communal Connectionmentioning
confidence: 99%
“…Early research on social connection identified the importance of an individual's perception of social inclusion as the determinant of belonging or loneliness (Cacioppo & Patrick, 2008). Perceived community support can increase resilience, enhance the evaluation of personal resources (Layous & Nelson-Coffey, 2020) and increase exercise motivation (Chen et al, 2014). A recent measure of community perception is the construct of KM.…”
Section: Km As Communal Connectionmentioning
confidence: 99%
“…Architectural Description Languages (ADLs) are languages proposed specifically to represent software architectures, which differentiate them from other languages that are applied for this purpose but not proposed for it (such as graphs and UML). Overwall, 10 studies used ADLs, among which the ADLs applied are: Dynamic Wright (ALLEN et al, 1998), SosADL (OQUENDO, 2016 and AADL (CHEN et al, 2014;ZHANG et al, 2016). One of the main advantages in the use of ADL's is the possibility of using tools for automatic validation and verification, assessing requirements such as performance and availability.…”
Section: Approaches To Represent Dynamic Software Architecturesmentioning
confidence: 99%